Effect of 8 Weeks of Physical Activity to Improve the Physical and Psychological State of 13 Women Under 30 Undergoing Treatment for Breast Cancer at the Saint Nicolas Clinic in Porto-Novo - YESSOUFOU, Lafiou; DOSSOU, Sémako Gérard; TIGRI, Tertutie Nawal; LAWANI, Mohamed Mansourou; HOUETO, Vignon Sègla Gratien; AGBAYAHOUN, Neddy Ornella Mahugnon (My University, 2022)
Abstract: Breast cancer is the most commonly diagnosed form of cancer in women. Several studies have shown the benefits of physical activity (PA) before and after treatment on the physical and psychological components of patients. Almost all of the studies mentioned are carried out on nonAfrican patients over the age of 40. And no experimental studies have been carried out in young patients undergoing treatment for breast cancer. This is how we asked ourselves the question of whether a physical exercise program carried out on young Beninese women under the age of 30 undergoing treatment for breast cancer at the Saint Nicolas clinic in Porto-Novo could it have the same effects on their physical and psychological components? Our objective through this research is to study the potential effect of a physical activity program on the physical and psychological state in women under 30 years old (27±5.8 years) undergoing treatment for a breast cancer at the Saint Nicolas clinic in Porto-Novo. An experimental study was then carried out with 13 patients (very low rate of women in this section suffering from breast cancer) undergoing treatment throughout 2022 at the Saint Nicolas clinic in Porto-Novo. The experimental group followed a physical activity program consisting of aerobic and muscular exercises; over a period of 8 weeks. According to the data collected and the feedback from the patients, the physical activity program seems to have been beneficial for most of them. There is an improvement in the quality of life and the physical condition of the patients. In addition, the management of physical fatigue and psychological fatigue also seem to improve. There was also a marked improvement in the ability to concentrate and self-esteem. The physical activity program has improved the physical and psychological state of Beninese women with breast cancer
Keywords: Breast cancer; Physical activity; Quality of life; Physical condition; Fatigue